PANDEMI COVID-19 IMPLIKASI BAGI PEMBIAYAAN BANK SYARIAH DI INDONESIA - Ana Zahrotun Nihayah; Lathif Hanafir Rifqi (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2021)
The Covid-19 pandemic is the result of the spread of coronavirus that occurs almost all over the world. In Indonesia, covid-19 first occurred on 02 March 2020. At that time, Indonesian citizen was infected by one of the Foreign Nationals of Japan. The transmission of covid-19 is increasing for a long time, until now covid-19 has spread in almost all 34 provinces in Indonesia. Health problems that further adversely affect almost all sectors of the industry, one of which is the Islamic banking industry. Therefore, the Financial Services Authority (OJK) issued several stimulus policies as a measure of anticipation of customers defaulting. This research is a descriptive study with the aim to determine the impact of pandemic covid-19 on Sharia bank financing in Indonesia. The samples used in this study were 11 Sharia commercial banks. The results showed that there are 8 Sharia commercial banks experiencing a downward trend in breeding, especially in April 2020. It can be concluded that the impact of covid-19 has a decrease in Sharia banking financing. Policies carried out by each Sharia commercial bank related to the anticipation of covid-19 to its financing activities, each bank implements a financing restructuring policy to debtors affected by the spread of covid-19